A New Theory to Explain the Underlying Pathogenetic Mechanism of Sudden Infant Death Syndrome - Lavezzi, Anna Maria (Frontiers in Neurology, 2015)
The Author, on the basis of her long experience on the neuropathology of SIDS, acquired through the study of a very wide set of cases, firstly identifies the neuronal centers of the human brainstem involved in the breathing control in perinatal life, with the pontine Kölliker-Fuse nucleus as main coordinator. What emerges from this analysis is that the prenatal respiratory movements differ from those post-natally in two respects: 1) they are episodic, only aimed at the lung development, and 2) they are abolished by hypoxia, not being of vital importance in utero, mainly to limit the consumption of oxygen. Then, as this fetal inhibitory reflex represents an important defense expedient, the Author proposes a new original interpretation of the pathogenetic mechanism leading to SIDS. Infants, in a critical moment of the autonomic control development, in hypoxic conditions could awaken the reflex left over from fetal life and arrest breathing, as he did in similar situations in prenatal life, rather than promote the hyperventilation usually occurring to restore the normal concentration of oxygen, with obviously a devastating outcome. This hypothesis is supported by immunohistochemical results showing in high percentage of SIDS victims, and not in age-matched infant controls, neurochemical alterations of the Kölliker-Fuse neurons, potentially indicative of inactivation. The new explanation of SIDS blames a sort of auto-inhibition of the KFN functionality, wrongly arisen with the same protective purpose to preserve life in utero, as trigger of the sudden infant death.